C1EIP Functions as an Activator of ENO1 to Promote Chicken PGCs Formation via Inhibition of the Notch Signaling Pathway - Jin, Kai; Li, Dong; Jin, Jing; Song, Jiuzhou; Zhang, Yani; Chang, Guobing; Chen, Guohong; Li, Bichun (Frontiers in Genetics, 2020)
The production of germ cells, especially primordial germ cells (PGCs), is important for avian stem cells and reproduction biology. However, key factors involved in the regulation of PGCs remain unknown. Here, we identified a PGC-related marker gene: C1EIP, whose activation and expression are regulated by transcription factor STAT3, histone acetylation, and promoter methylation. The C1EIP regulates PGC formation by mediating the expression of PGC-associated genes, such as CVH and CKIT. Knockout of C1EIP during the embryonic development reduced PGC generation efficiency both in vitro and in ovo. Conversely, overexpression of C1EIP increased the formation efficiency in vitro. C1EIP encodes a cytoplasmic protein that interacts with ENO1 in the cytoplasm and then ENO1 transfer to MBP1 impress Myc expression in nucleus via inhibits the Notch signaling pathway to positively regulates PGC generation. Collectively, our findings demonstrated C1EIP as a novel gene involved in PGC formation, which gene product regulates embryonic stem cell differentiation through the interaction with ENO1 and the subsequent inhibition of Notch signaling pathway via the impression of Myc.